The association between early neurological deterioration and whole blood purine concentration during acute stroke - Alexander J. Martin; Nicholas Dale; Christopher H. E. Imray; Christine Roffe; Craig J. Smith; Faming Tian; Christopher I. Price (BMC, 2019)
Abstract Background Early neurological deterioration (END) is common after stroke. Prediction could identify patients requiring additional monitoring and intervention. Purines, breakdown products of adenosine triphosphate which accumulate during acute hypoxia, may reflect the subclinical presence of vulnerable tissue. We considered whether whole blood purine concentration (WBPC) measurements during acute stroke were associated with subsequent END. Methods Patients within 4.5 h of stroke onset underwent point-of-care finger-prick measurement of WBPC and blinded assessment of symptom severity using the National Institutes of Health Stroke Scale (NIHSS). END was defined as an NIHSS increase ≥2 points at 24-36 h compared to baseline. Results 15/152 (9.8%) patients experienced END with a median [IQR] NIHSS increase of 4 [2-7] points. There were no strong associations between END and baseline NIHSS, clinical stroke subtype, thrombolytic therapy, physiological characteristics or time to assay. The median [IQR] WBPC concentration (uM) was higher before the occurrence of END but without statistical significance (7.21 [4.77-10.65] versus 4.83 [3.00-9.02]; p = 0.1). Above a WBPC threshold of 6.05uM, the risk of END was significantly greater (odds ratio 3.7 (95% CI 1.1-12.4); p = 0.03). Conclusion Although the study lacked statistical power, early WBPC measurement could be a convenient biomarker for identifying acute stroke patients at risk of END, but further evaluation is required.